BSA-Stabilized Mesoporous Organosilica Nanoparticles Reversed Chemotherapy Resistance of Anaplastic Thyroid Cancer by Increasing Drug Uptake and Reducing Cellular Efflux - Han, Xiao; Xu, Xiaoquan; Tang, Yuxia; Zhu, Feipeng; Tian, Ying; Liu, Wei; He, Doudou; Lu, Guangming; Gu, Yunfei; Wang, Shouju (Frontiers in Molecular Biosciences, 2020)
Anaplastic thyroid cancer (ATC) is a highly aggressive and the most lethal type of thyroid cancer. The standard-of-care for unresectable ATC is radiotherapy and chemotherapy, usually based on doxorubicin (Dox). However, most patients develop resistance shortly after treatment. To overcome the drug resistance, we synthesized the mesoporous organosilica nanoparticles (MONPs) loaded with Dox and stabilized the nanocomposites by bovine serum albumin (BSA). The surface area and pore volume of MONPs were 612.653 m2/g and 0.589 cm3/g. The loading capacity of DOX-MONPs reached 47.02%. Compared to Dox-MONPs and free Dox, BSA-Dox-MONPs had more durable tumor-killing power on both drug-sensitive cell line HTh74 and drug-resistant cell line HTh74R. The cellular uptake of BSA-Dox-MONPs was 28.14% and 65.53% higher than that of Dox-MONP in HTh74 and HTh74R. Furthermore, the BSA coating decreased the efflux rate of nanocomposites in HTh74 (from 38.95% to 33.05%) and HTh74R (from 43.03% and 32.07%). In summary, BSA-Dox-MONPs reversed the chemotherapy resistance of ATC cells via increased drug uptake and inhibited drug efflux, offering a promising platform for the treatment of chemo-resistant ATC.